问题 解答题
计算.
3
4
×
1
2
×24
7
8
×(
1
2
-
1
3
[
7
8
-(
1
6
+
1
3
)]÷
9
11
3
4
+
1
12
)×48
5
6
÷3+
1
6
×
1
3
13
97
×95+
26
97
答案

(1)

3
4
×
1
2
×24,

=

3
8
×24,

=9;

(2)

7
8
×(
1
2
-
1
3
),

=

7
8
×
1
6

=

7
48

(3)[

7
8
-(
1
6
+
1
3
)]÷
9
11

=[

7
8
-
1
2
9
11

=

3
8
×
11
9

=

11
24

(4)(

3
4
+
1
12
)×48,

=

3
4
×48+
1
12
×48,

=36+4,

=40;

(5)

5
6
÷3+
1
6
×
1
3

=

5
6
×
1
3
+
1
6
×
1
3

=(

5
6
+
1
6
)×
1
3

=1×

1
3

=

1
3

(6)

13
97
×95+
26
97

=

13
97
×95+
13
97
×2,

=

13
97
×(95+2),

=

13
97
×97,

=13.

问答题 简答题
单项选择题